PERAN PROGRAM UNIVERSITARIA RRI MEULABOH DALAM MENSOSIALISASIKAN PERGURUAN TINGGI DI KABUPATEN ACEH BARAT - Mursyidin Mursyidin (SOURCE : Jurnal Ilmu Komunikasi, 2017)
West Aceh Regency is an education center in the South West region of Aceh because it has seven universities, which consists of three state universities and four private universities. With the seven universities is expected to improve the quality of public education in West Aceh, one of them with the help of mass media such as local radio, Indonesian Republic Radio Meulaboh. This study focused on only two state universities, namely the University of Teuku Umar and the State Islamic Institute Meulaboh. This study used a qualitative approach with descriptive research method. The primary data source is the result of interview excerpts with informants, while the secondary data in the supporting documents. The data collection technique consists of the interviews, observation and documentation. IRR Meulaboh role in disseminating education can be seen from its programs 'Universitaria'. The program provides a space for University to be able to say hello to direct the public to provide the latest information through informants experts without the cost of socialization and education programs can reduce the information gap for people so that clarity and transparency in accessing information university met, especially for those who have the economic burden to continue education outside of the region to make the university in West Aceh as the main option. Keywords: west aceh, university, IRR meulaboh